Character building through non-formal education and parental collaboration in malaysia - Mohammad Fattah; Siti Kamilatul Fadhilah; Uci Andani; Riky Supratama; Warda Helwiyah (Yayasan Azhar Amanaa Yogyakarta, 2025)
This research deeply examines character building in productive age through non- formal education approach and strategic collaboration between parents and At- Tanzil Guidance Center, Serdang, Malaysia. Productive age is a crucial period in character building, but the lack of solid synergy between parents and non-formal education institutions often becomes an obstacle in achieving transformative results. Through a case study method with interview and observation techniques with parents, learners, and teachers, it was found that the active involvement of parents with programs in Sanggar significantly increased the motivation, discipline, responsibility, cooperation, and empathy of learners. This study recommends the development of more innovative programs and the strengthening of sustainable collaboration between families and non-formal education institutions. Various positive activities such as skills training and religious activities have proven to be able to be internalized into children's daily lives, especially when supported by the consistent role of parents at home. The role of parents is proven to be the main pillar in maintaining continuity and strengthening the impact of the education that has been initiated, making it a non-negotiable key factor in the success of character building. The survey results strongly suggest that the role of parents is not just important, but is a vital, strategic, and irreplaceable keyword in sustaining, strengthening, and ensuring the continuity of every educational achievement that has been pioneered in the Guidance Studio at tanzil serdang malaysia. Parental support, whether in the form of active involvement, intense communication with the school, or attention to the development of children's learning at home, is the main foundation for the success of the educational process. Without a strong synergy between schools and parents, all the efforts and educational programs that have been implemented will be difficult to achieve maximum and sustainable results.